Accurate measurement of elasticity of the radial artery wall considering changes in cross-sectional shape of artery caused by pushing pressure applied by ultrasound probe. (1st July 2022) - Shoji, Yuto; Mori, Shohei; Arakawa, Mototaka; Ohba, Shigeo; Kobayashi, Kazuto; Kanai, Hiroshi
Abstract: For the early diagnosis of atherosclerosis, our group developed an ultrasound probe that can simultaneously measure blood pressure and vessel diameter at the same position. However, because the developed probe requires the blood vessel to be deformed by pushing to measure the blood pressure, it affects the estimation of the vessel's elastic modulus. In the present study, we derived a series of equations to estimate the elastic modulus of a blood vessel considering the pushing pressure applied by the ultrasound probe and the resultant deformation of the blood vessel. The validity of the proposed method was verified by numerical calculations, and then the method was applied to in vivo measurements. The proposed method resulted in fewer variations in the elastic modulus estimates with different pushing pressures compared with the conventional method.